Étude de la Performance du Dispositif de Traitement des Eaux UsÉes par Boues ActivÉes de la ville d’Al- Hoceima, Maroc - Fouad Dimane; Khadija Haboubi; Issam Hanafi; Abdelouahad El Himri (European Scientific Journal, ESJ, 2016)
Morocco has taken over the desire to ensure sustainable development and to promote the treatment of domestic and industrial wastewater. In this context, several sewage treatment plants were created, in order to protect the environment from direct discharges of wastewater, and to hope for the reuse of treated wastewater. The use of Activated sludge process in treating the wastewater has been the solution to many problems. In order to evaluate the performance of wastewater treatment plant of the city of Al-Hoceima (North of Morocco). We studied the physico-chemical and bacteriological parameters; we carried out a series of measures such as: temperature, pH and conductivity, the biochemical oxygen demand BOD5, the chemical oxygen demands COD, fecal coliforms (FC) and total coliforms (TC). Measurement of the BOD5, COD and TSS yields values give respectively 96%, 95% and 85%. The tests showed that the treated water can be obtained with a quality complying with the agricultural reuse.